A patrimonialização do arquivo pessoal: análise dos registros Memória do Mundo do Brasil, da UNESCO - Duarte, Renato Crivelli [UNESP] (2013)
On the last decades the study with focus in personal records had been recurring in Brazil, which shows a growth in this thematic. Similarly, the concept of heritage has taken a central place in policy discussions related to the preservation worldwide. The development of studies on personal records shows the importance of these set of documents. Even sometimes seen as less important records, papers accumulated by a person have been increasingly recognized for their potential for representation of a historical period in society. This recognition is responsible to elevate its status within the government and scientific community, incising the concern to perseveration. On the heritage side, leads to the development of a broad sense related to the cultural and social status. Initially, only historical buddings and fine arts, preferentially religion related, where understood as part of the historical and cultural heritage especially in the Latin American reality. In present time, this sense was amplify drastically and new categories where created. Between these categories, surges the documental heritage. On concept less explored, responsible for more doubts and answers. Concern with this category, UNESCO, responsible for the coordination and developments of a series of preservation actions across the world, developed the Memory of World Program. This program has the objective to stimulate the preservation and access to records consider relevant for the mankind memory, as well to contribute to increase the status of this records. Brazil is a participant of this program and development since 2007 the selection of records holdings relevant for the cultural and national memory, which will integrated the Memory Of World Record. Between the years 2007 and 2010 a total of 38 holdings where nominated, 12 are personal... (Complete abstract click electronic access below)